National Writing Project's Multimodal Literacies and Teacher Collaboration: Enhanced Student Learning on Global Social Issues - Iyengar, Kalpana; Hood, Caleb (Texas Journal of Literacy Education, 2016)
Iyengar and Hood, both teacher consultants with the San Antonio Writing Project (SAWP), and instructors of an undergraduate society and social issues class, collaborated to enhance their undergraduate students' writing experiences using the National Writing Project model (Lieberman & Wood, 2003). Iyengar and Hood used strategies such as reflective essay writing, web-based tools (Hyler & Hicks, 2014), debate groups, and a research paper. Traditionally, the course required students to read chapters and report on the topics of the course. By adapting the National Writing Project's teaching strategy of writing and multimodal writing workshop, we made the course student-led and thus more engaging. This project was conducted at a major Hispanic serving institution of higher education in the Southwest of the US during the spring semester of 2016 and involved 220 students from four different sections of the course. The course was designed for education majors; all of the three courses were taught using classroom instruction with supplemental online resources. The paper argues that writing workshop method and multimodal literacies along with teacher collaboration enabled heightened student learning of a variety of global issues. The researchers used pre and posttest surveys addressing students' responses to social justice issues. The post survey narrative responses indicated greater consciousness of the course concepts related to social issues.
Keywords: Essays; Global Education; Group Discussion; Literacy; Models; Social Justice; Social Problems; Teacher Collaboration; Teaching Methods; Technology Integration; Undergraduate Students; Writing Processes; Writing Workshops